Myosteatosis as an independent predictor for all-cause and cardiac mortality in initial-dialysis patients: a multicenter, retrospective cohort study - Hou, Shi-Mei; Li, Min; Cao, Jing-Yuan; Wang, Yao; Yang, Min; Tian, Li; Ni, Yan-Hong; Yang, Bi-Xia; Hao, Li-Rong; Hao, Jian-Bing; Zou, Chun-Bo; Zhang, Shu-Yan; et al. (Frontiers in Physiology, 2025)
BackgroundMyosteatosis is associated with adverse prognosis in diseases. We aimed to establish thresholds for myosteatosis, assess its association with all-cause and cardiac mortality in initial dialysis patients, and construct a myosteatosis-based survival nomogram. assessed the predictive value of myosteatosis with all-cause and cardiac mortality in initial-dialysis patients, and constructed a myosteatosis-based survival nomogram.MethodsThis multicentric retrospective study included 383 initial-dialysis patients (1/2014–12/2019). Endpoints include all-cause and cardiac mortality. Skeletal Muscle Index (SMI, cm2/m2) and Skeletal Muscle Density (SMD, Hounsfield Units [HU]) were measured at the third lumbar vertebra (L3) level by computed tomography (CT). Sex-specific SMI and SMD thresholds predicted all-cause mortality through the receiver operating characteristic (ROC) curves. The Cox models assessed myosteatosis-associated mortality risks. Survival prediction models were built using univariate and multivariate Cox proportional hazards regression in the training cohort, followed by internal and external validation.ResultsPatients were predominantly aged 18–65 years (n = 298, 77.81%), with males comprising 60.84% (n = 233). All-cause mortality was 22.72% (n = 87), of which 52.87% (n = 46) were attributed to cardiac causes. Sex-specific SMD cutoffs for predicting all-cause mortality were 32.46 HU (AUC = 0.707) in males and 34.58 HU (AUC = 0.690) in females (both P < 0.05). Myosteatosis was associated with higher all-cause (36.7%) and cardiac mortality (19.8%) (both P < 0.001), and independently predicted both outcomes (all-cause mortality: HR = 3.203, 95% CI:1.937–5.296; cardiac mortality: HR = 3.418, 95% CI:1.718–6.802). The myosteatosis-based nomogram achieved a C-index of 0.761, validated in real-world data.ConclusionSex-specific myosteatosis thresholds (males: SMD ≤32.46 HU; females: ≤34.58 HU) derived from L3-CT independently predicted all-cause and cardiac mortality in initial-dialysis patients. The myosteatosis-based survival nomogram demonstrated moderate-to-good predictive accuracy and potential clinical utility.